Core Concepts and Contemporary Issues in Privacy (AMINTAPHIL: The Philosophical Foundations of Law and Justice,, 2018)
This book offers a comprehensive investigation of privacy in the modern world. It collects 16 papers that look at this essential topic from many facets, from the personal to the technological, from the philosophical to the legal. The contributors examine such issues as the value of privacy protection, the violation of spreading personal falsehoods, the digital rights of children, an individual's right to be forgotten from internet search engines, and more. The organization of the volume helps provide a nuanced understanding of this often controversial topic. Coverage starts with key concepts before moving on to explore personal information privacy and the impact of new technologies. Next, the papers consider privacy in different contexts. These include work, sex, family, crime, and religion. This structure enables greater engagement with the difficult questions about privacy. Readers will gain deep insight into the core concepts of privacy as well as its application to everyday life. This interdisciplinary volume brings together an international team of scholars. They provide a broad combination of expertise in law, philosophy, and political science. Overall, this thought-provoking examination will appeal to interested readers in both academia and practice. .